2020
DOI: 10.1177/1055665620956872
|View full text |Cite
|
Sign up to set email alerts
|

The Method of Surgical Lip Repair Affects Speech Outcomes in Children With Bilateral Cleft Lip and Palate

Abstract: Objective: It was hypothesized that lip repair protocols in children with bilateral cleft lip and palate (BCLP) would affect development of bilabial consonants /m/ /b/ /p/. This study compared speech outcomes in 2 surgical groups. Design: A retrospective case note investigation. Setting: UK Cleft Centre (2000-2009). Patients: Forty-nine children with complete BCLP, of whom 26 had a 1-stage and 23 a 2-stage bilateral cleft lip repair. Interventions: One-stage cleft lip repair versus a 2-staged cleft lip repair.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The timing of lip repair showed a weak but consistent association with structural speech outcomes, a later lip repair being associated with poorer structural scores and an earlier repair with better structural outcomes. Lip repair has not previously been thought to have an impact on speech outcomes in unilateral cleft lip and palate, although a recent study of speech outcomes in bilateral cleft lip and palate has suggested that lip repair may impact on articulation outcomes 36 . Later lip repair in this study may be confounded with the width of the cleft, however, and cleft width has been shown to affect speech outcomes including structure 9 …”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The timing of lip repair showed a weak but consistent association with structural speech outcomes, a later lip repair being associated with poorer structural scores and an earlier repair with better structural outcomes. Lip repair has not previously been thought to have an impact on speech outcomes in unilateral cleft lip and palate, although a recent study of speech outcomes in bilateral cleft lip and palate has suggested that lip repair may impact on articulation outcomes 36 . Later lip repair in this study may be confounded with the width of the cleft, however, and cleft width has been shown to affect speech outcomes including structure 9 …”
Section: Discussionmentioning
confidence: 66%
“…Lip repair has not previously been thought to have an impact on speech outcomes in unilateral cleft lip and palate, although a recent study of speech outcomes in bilateral cleft lip and palate has suggested that lip repair may impact on articulation outcomes. 36 Later lip repair in this study may be confounded with the width of the cleft, however, and cleft width has been shown to affect speech outcomes including structure. 9…”
Section: Surgical Factors Associated With Speech Outcomes -Timing Of ...mentioning
confidence: 85%
“…A recent report suggested that early treatment factors, such as type of lip repair, may play a role in determining risk for articulation disorders in CL AE A. 21 Although some may attribute the risk of speech disorders in CL AE A to structural lip or dentalocclusal factors, this would only explain the occurrence of isolated articulation disorders affecting anterior speech sounds and/or those most sensitive to dental-occlusal abnormalities. A more compelling rationale for communication disorders in children with CL AE A is a genetic or neurodevelopmental etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies with standard assessment procedures and timepoints for patient evaluations would produce more robust and valid estimates of risk. A recent report suggested that early treatment factors, such as type of lip repair, may play a role in determining risk for articulation disorders in CL ± A 21 . Although some may attribute the risk of speech disorders in CL ± A to structural lip or dental-occlusal factors, this would only explain the occurrence of isolated articulation disorders affecting anterior speech sounds and/or those most sensitive to dental-occlusal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…To improve speech outcomes, it is important to identify groups within the CP±L population who may be most at risk for a poor speech outcome at age 5. Children with Robin Sequence [6], and children with Bilateral Cleft Lip and Palate (BCLP) who have undergone lip adhesion [7] have been identified as potential 'at risk' groups for poor speech outcomes at age 5. Given the prevalence of conductive hearing loss in this population [1,8] it is important to consider what effect this may have on speech development.…”
Section: Introductionmentioning
confidence: 99%